2013
DOI: 10.1002/cctc.201300246
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Silica‐Supported Ruthenium Phosphine Catalysts for Selective Formic Acid Decomposition

Abstract: The water‐soluble ruthenium(II)–mTPPTS complex (mTPPTS=meta‐trisulfonated triphenylphosphine) efficiently catalyzes the generation of hydrogen from formic acid in aqueous solution. This catalyst has been immobilized in a hydrophilic silica support to facilitate mobile portable applications. It was used in diluted formic acid solutions, in which the recycling of a liquid phase catalyst is problematic. A series of heterogenized catalysts have been prepared by the reaction of the ruthenium(II)–mTPPTS dimer and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 63 publications
0
59
0
2
Order By: Relevance
“…However, reports of highly active and stable catalysts in aqueous solution are scarce. 16, [46][47][48] We recently reported that a five-membered azole moiety is an efficient electron donor, and its incorporation into a catalyst complex is effective for FA dehydrogenation in water. 49 This is supposedly due to the high electron donating ability of the azole moieties.…”
mentioning
confidence: 99%
“…However, reports of highly active and stable catalysts in aqueous solution are scarce. 16, [46][47][48] We recently reported that a five-membered azole moiety is an efficient electron donor, and its incorporation into a catalyst complex is effective for FA dehydrogenation in water. 49 This is supposedly due to the high electron donating ability of the azole moieties.…”
mentioning
confidence: 99%
“…[10] Catalytic FA decomposition is well known and can be achieved using avariety of transition metal complexes and supported metal catalysts.P articularly Ru/PR 3 and Ir/bipyridine complexes are highly active and selective for the synthesis and decomposition of FA. Laurenczy et al [15] tethered Ru/ TPPTS on phosphine-modified MCM41 and reported TOFs up to 2780 h À1 at 110 8 8C. [12] Nevertheless,f or the continuous decomposition of large volume streams of aqueous FA,h eterogeneous catalysts are required.…”
mentioning
confidence: 99%
“…Further work to attach the catalyst to a hydrophilic silica catalyst with varying linker-lengths was therefore conducted. It was reported that the short linker distances in particular could have a positive effect on the turnover frequencies of the catalyst whilst overcoming some of the stability limitations of the homogenous systems [44].…”
Section: Supported Catalystsmentioning
confidence: 99%